Properties of EPS RHA lighweight concrete bricks under different curing conditions - Teo, DCL; Ling, I.H (ScienceDirect, 2011)
The depletion of non-renewable resources has become an alarming issue nowadays. Many environmentalists and researchers have been investigating the use of waste materials as a renewable resource for use especially as raw materials in construction. This paper reports on the potential use of waste rice husk ash (RHA) and expanded polystyrene (EPS) beads in producing lightweight concrete bricks. The RHA was used as a cementitious material since it is a lightweight reactive pozzolanic material. RHA was used as partial cement replacement, while the EPS was used as partial aggregate replacement in the mixes. Bricks of 215 mm × 102.5 mm × 65 mm in size were prepared in this study. The engineering properties of the bricks were investigated. Among the properties studied were hardened concrete density, compressive strength and water absorption of the EPS RHA concrete bricks. Scanning electron microscopy (SEM) analysis was also performed on the brick samples. Four types of curing conditions were employed in this study. These include full water curing, air dry curing, 3-day curing and 7-day curing. It was found that the properties of the bricks are mainly influenced by the content of EPS and RHA in the mix and also the curing condition used.